Hope and social support as the predictors of self-esteem among postgraduate international students - Amoushahi, Mohsen, 1976-; Aqeel Khan, supervisor; Fakulti Pendidikan (2013)
Thesis (Sarjana Pendidikan (Bimbingan dan Kaunseling)) - Universiti Teknologi Malaysia, 2013